Knowledge, awareness on breast cancer, and practice of breast self-examination using virtual reality among community in Kuantan: a cross-sectional study - Sowtali, Siti Noorkhairina; Abdul Rahman, Ahmad Nu'man; Awalludin, Azzah Quratuaini (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2025)
Introduction: The World Health Organization Global Breast Cancer Initiative aims to prevent 2.5 million breast cancer deaths worldwide between 2020 and 2040. Recently, virtual reality (VR) has been deemed to be a promising tool to improve public awareness of breast cancer through immersive experiences. This study aimed to provide baseline information on the level of knowledge and awareness of breast cancer as well as the practice of breast self-examination using VR among the community near the International Islamic University Malaysia (IIUM) Kuantan Campus. Materials and methods: A cross-sectional study was conducted among Kuantan residents, consisting of university staff, students, and the general population through convenience sampling (n = 64). A set of questionnaires was pre-tested among 18 Kuantan residents and was later utilised for the preliminary findings. The data obtained was analysed using SPSS version 28. Results: The content validation index was 97.5% with a reliability of 0.89. The median age of the respondents was 22.00 (3), female (82.8%), Malay (93.8%), and non-married (90.6%). The median score for knowledge of breast cancer risk factors was 13.00 (3), knowledge regarding breast cancer signs and symptoms was 9.00 (2), awareness of breast cancer and breast self-examination was 77.00 (20), and the practice of breast self-examination was 64.00 (36). Conclusion: These preliminary findings revealed that the majority of the respondents possessed an above-satisfactory level of knowledge of breast cancer risk factors, signs and symptoms, as well as a moderate practice of breast self-examination. The findings of this study suggest that the VR approach to breast cancer awareness programmes has the potential to increase public awareness of breast cancer.